Endemic Fungi Presenting as Community-Acquired Pneumonia: A Review - Azar, Marwan M.; Malo, Joshua; Hage, Chadi A. (Seminars in Respiratory and Critical Care Medicine, 2020)
In endemic areas, dimorphic fungal infections due to Histoplasma capsulatum, Blastomyces dermatitidis, and Coccidioides posadasii/immitis account for up to 30% of cases of community-acquired pneumonia. Because respiratory manifestations are often indistinguishable from common bacterial causes of pneumonia, the diagnosis of pulmonary histoplasmosis, blastomycosis, and coccidioidomycosis is often delayed and associated with antibiotics overuse. In addition to being highly endemic to certain regions of North America, dimorphic fungi have global significance due to established areas of endemicity in all six inhabited continents, an increasingly interconnected world of travelers and transported goods, and a changing epidemiology as a result of global heating and anthropomorphic land utilization. In this review, we discuss the epidemiology, pathogenesis, clinical presentation, diagnostic modalities, and treatment strategies for histoplasmosis, blastomycosis, and coccidioidomycosis.
Keywords: histoplasmosis; blastomycosis; coccidioidomycosis; community-acquired pneumonia